2016
DOI: 10.1111/jeb.12867
|View full text |Cite
|
Sign up to set email alerts
|

Is specialization an evolutionary dead end? Testing for differences in speciation, extinction and trait transition rates across diverse phylogenies of specialists and generalists

Abstract: Specialization has often been claimed to be an evolutionary dead end, with specialist lineages having a reduced capacity to persist or diversify. In a phylogenetic comparative framework, an evolutionary dead end may be detectable from the phylogenetic distribution of specialists, if specialists rarely give rise to large, diverse clades. Previous phylogenetic studies of the influence of specialization on macroevolutionary processes have demonstrated a range of patterns, including examples where specialists have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
86
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 67 publications
9
86
2
Order By: Relevance
“…We found that the complexity of venom components was lower for specialists than for generalists. Specialization is more derived compared to an assumed ancestral generalist state (e.g., Day, Hua, & Bromham, ; PekĂĄr, Coddington, & Blackledge, ). This seems to contradict the classical theory of venom evolution, which is based on frequent gene duplication, positive selection and protein neofunctionalization (KordiĆĄ & GubenĆĄek, ), and should lead to more complex arsenal.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the complexity of venom components was lower for specialists than for generalists. Specialization is more derived compared to an assumed ancestral generalist state (e.g., Day, Hua, & Bromham, ; PekĂĄr, Coddington, & Blackledge, ). This seems to contradict the classical theory of venom evolution, which is based on frequent gene duplication, positive selection and protein neofunctionalization (KordiĆĄ & GubenĆĄek, ), and should lead to more complex arsenal.…”
Section: Discussionmentioning
confidence: 99%
“…1993; Day et al. 2016). However, failure to diversify or transition back to an ancestral state does not signify a lack of success per se.…”
Section: Discussionmentioning
confidence: 99%
“…Day et al. (2016) found mixed support for the evolutionary dead‐end hypothesis for specialists across a set of 10 phylogenies. In general, however, these studies focus on groups with either a small number of specialized taxa or with very few replicated events of specialist evolution.…”
mentioning
confidence: 99%
“…The decrease of specialist species in an ecosystem can be a major threat to global biodiversity (Clavel, Julliard, & Devictor, ). However, comparative studies often fail to find higher extinction rates in specialists than in generalists (Day, Hua, & Bromham, ; Stern et al, ; Tripp & Manos, ). Therefore, whether ecological specialization determines the fate of a species remains controversial (Day et al, ; Stern et al, ).…”
Section: Introductionmentioning
confidence: 99%